2018
DOI: 10.1186/s41927-018-0026-7
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of patients, first-degree relatives and rheumatologists on preventive treatments for rheumatoid arthritis: a qualitative analysis

Abstract: Background There is growing evidence that it may be possible to identify people at high risk of developing rheumatoid arthritis (RA). Assuming that effective interventions were available, this could mean that treatments introduced in the pre-symptomatic phase could prevent or delay the onset of the disease. Our study aimed to identify the potential attributes involved in decision-making around whether or not to take preventive treatment for RA, in order to inform the development of a discrete choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 38 publications
4
40
0
Order By: Relevance
“…The finding that first-degree relatives were more hesitant about preventive medication is in agreement with how patients with RA in previous research felt that their family members might react if given the option of preventive medicine [30]. In line with findings from previous research in RA (e.g [27, 39]), potential side effects, long-term implications of taking the medication and possible interactions with existing conditions and medications were a major concern for many of our interviewees and they indicated that they would weigh up perceived benefits and potential harms before making a decision about therapy. Personal experiences of RA in family members influenced decision making about the value of preventive medication for several interviewees.…”
Section: Discussionsupporting
confidence: 89%
“…The finding that first-degree relatives were more hesitant about preventive medication is in agreement with how patients with RA in previous research felt that their family members might react if given the option of preventive medicine [30]. In line with findings from previous research in RA (e.g [27, 39]), potential side effects, long-term implications of taking the medication and possible interactions with existing conditions and medications were a major concern for many of our interviewees and they indicated that they would weigh up perceived benefits and potential harms before making a decision about therapy. Personal experiences of RA in family members influenced decision making about the value of preventive medication for several interviewees.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, rheumatologists were more willing to prescribe preventive medication than individuals at risk of RA were willing to use medication. This is an important finding since the manner in which benefits and risks of treatment are presented to at-risk individuals influences health decisions and a positive attitude of the rheumatologist may encourage at risk individuals to decide for intervention [17]. However, minor side effects did not affect the rheumatologists' decision to start medication, while it is a significant concern for at risk individuals.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies in first-degree relatives (FDRs) of RA patients showed that many were willing to make lifestyle changes such as weight loss or diet changes and that their willingness to start preventive medication was primarily influenced by perceived risk of RA development, medication effectiveness, and potential side effects [ 13 15 ]. Furthermore, the opinion of the health care professional might be an important attribute involved in the patient’s decision whether or not to take preventive treatment [ 16 , 17 ]. However, FDRs are mainly asymptomatic individuals and perceptions in this group may differ from symptomatic at risk individuals [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore important to understand patients' perspectives in this context to identify barriers and facilitators to approaches targeting first-degree relatives. This was the focus of a UK based qualitative study 52 Preferences for interventions to reduce risk of developing RA Several European qualitative studies have explored preferences relating to preventive interventions for RA of first-degree relatives [58][59][60] , RA patients 52,59 , and ACPA positive individuals without arthritis. 53 Lifestyle change was preferred over pharmacological interventions to reduce RA risk 52, 53, 58-60 , however positive viewpoints were associated with the perspective that any intervention would need to substantially reduce or completely remove their risk of RA.…”
Section: Reliable Access To First Degree Relatives Is Usually Indirecmentioning
confidence: 99%
“…64 A similar North American study sought perspectives from patients with RA, first-degree relatives of including people with the disease and health care professionals. 59 Preferences elicited from subsequent discrete choice experiments suggested that the decision to take preventive medication will depend primarily on factors other than the reduction in risk of RA. 65,66 For first-degree relatives of patients this is more likely to be how treatment is taken, the opinion of the health care professionals, and the potential risk and reversibility of side effects.…”
Section: Reliable Access To First Degree Relatives Is Usually Indirecmentioning
confidence: 99%